The invisible hand in economics how economists explain unintended social consequences - Aydinonat, N. Emrah. (Routledge INEM advances in economic methodology ;, 2008)
Addressing theÈcontroversial concept ofẗhe invisible hand, this book questions, examines and explicates the strengths and weaknesses of the concept by analyzing its paradigmatic examples such as Carl Menger's Origin of Money and Thomas Schelling's famous checkerboard model of residential segregation.